Membrane Microvesicles as Potential Vaccine Candidates - Shkair, Layaly (Int J Mol Sci, 2021)
The prevention and control of infectious diseases is crucial to the maintenance and protection of social and public healthcare. The global impact of SARS-CoV-2 has demonstrated how outbreaks of emerging and re-emerging infections can lead to pandemics of significant public health and socio-economic burden. Vaccination is one of the most effective approaches to protect against infectious diseases, and to date, multiple vaccines have been successfully used to protect against and eradicate both viral and bacterial pathogens. The main criterion of vaccine efficacy is the induction of specific humoral and cellular immune responses, and it is well established that immunogenicity depends on the type of vaccine as well as the route of delivery. In addition, antigen delivery to immune organs and the site of injection can potentiate efficacy of the vaccine. In light of this, microvesicles have been suggested as potential vehicles for antigen delivery as they can carry various immunogenic molecules including proteins, nucleic acids and polysaccharides directly to target cells. In this review, we focus on the mechanisms of microvesicle biogenesis and the role of microvesicles in infectious diseases. Further, we discuss the application of microvesicles as a novel and effective vaccine delivery system.